1997
DOI: 10.1017/s0033822200018713
|View full text |Cite
|
Sign up to set email alerts
|

The First 14C Dating of Monuments in European Scythia

Abstract: The first radiocarbon dates for the famous monuments of European Scythia were produced for the Kelermes, Seven Brothers, Solocha and Chertomlyk barrows (burial mounds) by both accelerator mass spectrometry (AMS) and conventional methods. The obtained 14C dates confirmed the traditional archaeological chronology, which was based on the analysis of written data and typological comparisons of Scythian artifacts with similar objects found in the Ancient East and Greece. The 14C dates for the European Scythian monu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…It was concluded that a climate change to cooler, wetter conditions occurred in the temperate and boreal zones of Europe, North-and South America, Japan and New Zealand. In addition to the paleoclimatological-archaeological evidence as mentioned by van Geel (Zaitseva et al 1998), and thus also may correspond to the period of the sharply rising 14C content of the atmosphere.…”
Section: ± 35mentioning
confidence: 71%
See 1 more Smart Citation
“…It was concluded that a climate change to cooler, wetter conditions occurred in the temperate and boreal zones of Europe, North-and South America, Japan and New Zealand. In addition to the paleoclimatological-archaeological evidence as mentioned by van Geel (Zaitseva et al 1998), and thus also may correspond to the period of the sharply rising 14C content of the atmosphere.…”
Section: ± 35mentioning
confidence: 71%
“…In addition to the paleoclimatological-archaeological evidence as mentioned by van Geel, Buurman and Waterbolk, new 14C dates from the earliest Scythian grave monuments in Europe may indicate that extreme climatological conditions in Central Asia triggered the migration of Scythians to southeast Europe and western Asia. The oldest dates of the Kelermess monuments (northwest Caucasus) are 2690 ± 150 and 2610 ± 60 BP (Zaitseva et al 1998), and thus also may correspond to the period of the sharply rising 14C content of the atmosphere.…”
Section: ± 35mentioning
confidence: 99%
“…The most ancient known Scythian monument in Europe (Steblev group barrows, grave 15, located on the right bank of the Dnieper River) has been dated to the 8th century BC. Based on data published by Zaitseva et al (1998), had previously suggested a link between the migration of Scythians to southeast Europe and climate change, but they assumed that the trigger was an episode of 'extreme climate', without a comprehensive understanding of the triggering (negative or positive) environmental factors. Based on new data, we present the hypothesis that the solar-driven climatic change to wetter conditions was of crucial importance for the cultural blooming and expansion of the Scythian culture.…”
Section: Introductionmentioning
confidence: 99%